High-Methionine Diet Attenuates Severity of Arthritis and Modulates IGF-I Related Gene Expressions in an Adjuvant Arthritis Rats Model - Mingxin Li; Lidong Zhai; Wanfu Wei (Mediators of Inflammation)
Rheumatoid arthritis, a synthesized form of adjuvant arthritis exhibited throughout many animal species, inhibits liver function and circulation of IGF-I and contributes to the degradation of skeletal muscle mass. One of the primary goals of the present study is determining whether a high-Methionine (high-Met) diet is capable of reducing the adverse effects of arthritis, namely, loss of body mass. Following adjuvant injection, forty arthritic rats were randomly assigned to either a control group with a basal diet or a high-Met group with the same basal diet + 0.5% Methionine. After 14 days all rats were terminated. The high-Met group exhibited an increase in body weight and food intake in comparison with the control group (P<0.05). High-Met diet debilitated arthritis-induced surges in the gastrocnemius in both atrogin-1 and the MuRF1 expressions; however, it was observed to have little to no effect on atrogin-1 and MuRF1 gene expression in soleus. At the same time, high-Met diet rats experienced a rise in IGF-I, with lowering of IGFBP-3 gene expression in the gastrocnemius and the soleus. These data suggest that arthritis severity can be partly attenuated by high-Met diet.